1996
DOI: 10.1093/milmed/161.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Successful Navy Submarine Personnel

Abstract: This study evaluated the personality characteristics of senior enlisted and occupationally successful Navy submarine personnel. One hundred subjects completed the Schedule for Nonadaptive and Adaptive Personality (SNAP). Results indicated that the traits of detachment, propriety, and workaholism were most descriptive of the sample. Thirty-seven percent met SNAP criteria for a personality disorder, typically antisocial, obsessive-compulsive, or avoidant. The results are discussed in terms of adaptation to envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…The SNAP's diagnostic scales are also being used in research and clinical settings (e.g., Moes, Lall, & Johnson, 1996), but much less information is available regarding their psychometric properties. Items are similar to the criteria for PDs in the Diagnostic and Statistical Manual of Mental Disorders (4th ed.)…”
mentioning
confidence: 99%
“…The SNAP's diagnostic scales are also being used in research and clinical settings (e.g., Moes, Lall, & Johnson, 1996), but much less information is available regarding their psychometric properties. Items are similar to the criteria for PDs in the Diagnostic and Statistical Manual of Mental Disorders (4th ed.)…”
mentioning
confidence: 99%
“…Likewise, certain dispositional traits associated with adaptive coping have been described among US Navy (USN) submarine crews, including detachment, propriety, and workaholism (Moes, Johnson, & Lall, 1996), and South African Navy (SAN) submariners, including adventurousness, confidence, group orientation, and precision (Van Wijk & Waters, 2000). Both SAN divers and submariners score high on sense of coherence scales, suggesting a positive dispositional orientation to life (Van Wijk, 2008).…”
Section: Coping In the Context Of Extreme Environmentsmentioning
confidence: 99%
“…Relatively homogenous psychological profiles have been reported for these specialists (e.g., divers : Beckman et al, 1996;Van Wijk & Waters, 2001; or submariners: Moes et al, 1996;Van Wijk & Waters, 2000), who are also exposed to the same potential stressors and environmental demands (e.g., Suedfeld & Steel, 2000). The first study thus aimed to investigate whether members of these specialist groups would then also favor similar coping response styles.…”
Section: Objectivesmentioning
confidence: 99%
“…Slater 25 noted that obsessional neurosis in soldiers seemed to be more closely associated with preexistent personality traits than most other neurotic disorders. Of occupationally successful submariners in the US Navy cohort, 9% met criteria for obsessive-compulsive personality disorder, 26 and one study found that officers may be more likely to possess obsessional 'features' than other ranks. 27 In another study, obsessive-compulsive, depressive and anxiety symptoms were more common in a cohort of Chinese officers over 30 years of age.…”
Section: Obsessive-compulsive Symptomsmentioning
confidence: 99%